A multi-stakeholder strategy to identify conservation priorities in Peninsular Malaysia - Nagulendran, Kangayatkarasu; Padfield, Roryd; A. Aziz, Sheema; Amir, A. Aldrie; Abd. Rahman, Abd. Rahim; A. Latiff, Mohamad; Zafir, Ahmad; Quilter, Aida Ghani; Tan, Ange; Arifah, Sharifuddin; Awang, Noor; Azhar, Noraini; et al. (Cogent OA, 2016)
Malaysia, with its rapidly growing economy, exemplifies the tensions between conservation and development faced by many tropical nations. Here we present the results of a multi-stakeholder engagement exercise conducted to (1) define conservation priorities in Peninsular Malaysia and (2) explore differences in perceptions among and within stakeholder groups (i.e. government, academia, NGOs and the private sector). Our data collection involved two workshops and two online surveys where participants identified seven general conservation themes and ranked the top five priority issues within each theme. The themes were: (1) policy and management, (2) legislation and enforcement, (3) finance and resource allocation, (4) knowledge, research and development, (5) socio-economic issues, (6) public awareness and participation and (7) rights of nature. In spite of their very different backgrounds and agendas, the four stakeholder groups showed general agreement in their priority preferences except for two issues. Respondents from government and private sector differed the most from each other in their priority choices while academia and NGO showed the highest degree of similarity. This ranked list of 35 conservation priorities is expected to influence the work of policy-makers and others in Peninsular Malaysia and can be used as a model to identify conservation priorities elsewhere.